UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA AUDIO VISUAL PADA SISWA KELAS VIII SMP - Nurbaiti, Ida (Epsilon: Jurnal Pendidikan Matematika, 2019)
Abstract: This study aims to improve the activities and learning outcomes of students of class VIII Odd Semester SMP Negeri 36 Bandar Lampungusing audio visual media. This research is Classroom Action Research (CAR). The research subjects were students of class VIII-H of SMP Negeri 36 Bandar Lampung, with 35 students. The study was conducted in three cycles. The research data were obtained from observations of student mathematics learning activities as well as student mathematics learning achievement test items. The results of this study indicate that learning mathematics by using audio visual media can improve the activities and learning outcomes of students of class VIII Odd Semester SMP Negeri 36 Bandar Lampung. This is reinforced by the results of observations in class that show the average percentage of students' mathematics learning activities in the first cycle is 40% in the least active criteria while in the second cycle increases to 75% are in the active criteria and in the third cycle increases to 97 % on very active criteria. Then also supported by the percentage of student graduation that is increasing from 0% in the first cycle, 51% in the second cycle and 89% in the third cycle. Thus it can be concluded that by using audio-visual media can improve the activities and learning outcomes of students of class VIII Odd Semester SMP Negeri 36 Bandar Lampung.